GE_GERICHTE C/19403/2014 vom 8. Mai 2015 - GE Cour de justice (2015)
LOGEMENT DE LA FAMILLE; PROTECTION DE L'UNION CONJUGALE; OBLIGATION D'ENTRETIEN; CONJOINT; DÉBUT | CC.173.3; CC.176.1.2; CPC.58.1; CPC.271.a; CPC.316.3